Paraguay : Financial System Stability Assessment: Update. (IMF Staff Country Reports; Country Report ;, 2011)
Most banks in Paraguay appear resilient to shocks, although the exposure to large borrowers is high. The mission strongly recommends the adoption of measures that would moderate credit growth and induce financial institutions to build cushions that can protect them and their clients from a sudden reversal of conditions. Paraguay's banking system safety net is well developed. To start building a strong macroprudential policy framework, Executive Directors recommend improving coordination and information sharing among all agencies responsible for financial stability and financial sector oversight.